2016
DOI: 10.1017/s1041610216001009
|View full text |Cite
|
Sign up to set email alerts
|

Stressors and anxiety in dementia caregiving: multiple mediation analysis of rumination, experiential avoidance, and leisure

Abstract: The results suggest that caregivers' experiential avoidance, rumination, and leisure satisfaction may function as mechanisms through which BPSD influence on caregivers' anxiety. Training caregivers in reducing their levels of experiential avoidance and rumination by techniques that foster their ability of acceptance of their negative internal experiences, and increase their level of leisure satisfaction, may be helpful to reduce their anxiety symptoms developed by stressors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…In addition, rumination explained the association between behavioral/ emotional problems in a person with ABI and caregivers' symptoms of anxiety and depression. This result is consistent with findings of studies that show that stressors lead to greater use of rumination (Barchia & Bussey, 2010), something found in studies with family caregivers (Romero-Moreno et al, 2016), where caregivers who reported having more stressors also reported a higher level of rumination.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, rumination explained the association between behavioral/ emotional problems in a person with ABI and caregivers' symptoms of anxiety and depression. This result is consistent with findings of studies that show that stressors lead to greater use of rumination (Barchia & Bussey, 2010), something found in studies with family caregivers (Romero-Moreno et al, 2016), where caregivers who reported having more stressors also reported a higher level of rumination.…”
Section: Discussionsupporting
confidence: 91%
“…The role of rumination has also been examined in different samples of family caregivers, being associated with higher levels of distress, such as anxiety and depression, experienced by a caregiver (Perlick et al, 2012). In addition, Romero-Moreno et al (2016) found that rumination mediated the association between stressors and anxiety in family caregivers of people with dementia.…”
Section: Article In Pressmentioning
confidence: 99%
“…Psychology, accessibility, time, partners, and security factors can all become crucial leisure constraints [33]. Stressors may influence anxiety through its effect on satisfaction with leisure activities [34]. Regular leisure activities can mitigate stress and depression [35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dementia family caregivers also show low levels of quality of life (Coen, O'Boyle, Coakley, & Lawlor, ) and high levels of anxiety (Joling et al, ). Further, emotion‐regulation variables have been found to influence in caregivers' anxiety levels, such as emotional intelligence (Weaving, Orgeta, Orrell, & Petrides, ) and rumination (Romero‐Moreno, Losada, Márquez‐González, & Mausbach, ). Future studies should also analyse the association between ambivalence, guilt feelings, and emotion‐regulation variables in dementia family caregivers.…”
Section: Discussionmentioning
confidence: 99%